Strategi Pemasaran Agen PT Sun Life - Alfin Agung Azhar; Nuri Aslami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
The purpose of this study is to analyze the marketing strategies used by insurance agents in finding Sun life insurance accounts. This study uses descriptive and qualitative methods which include observation, library science, documentation, data processing, data presentation, and reasoning. According to the survey, researchers follow a cycle to plan, seek, approach, find, present facts, and end objections to the specific address of the insurance agent receiving the payment. Insurance agents often refer customers, often visit individuals, provide detailed explanations and insights about insurance, provide excellent information and service, and provide customers with excellent information and services to retain and improve their customers. Available anytime when you need insurance assistance, which is any day or time. Keywords: marketing strategy, insurance agent, sunlife.